Determinants of Intrauterine Contraceptive Device Utilization at Primary Health Care Facilities in Mekelle City, Northern Ethiopia - Temesgen, Gebremaryam; Gebrehiwot, Haftom; Hussen, Sultan; Shegaze, Mulugeta; Tolosie, Kabtamu; Boti, Negussie (Ethiopian Journal of Reproductive Health, 2021)
Abstract Background: Each year, the current level of modern contraceptive use averts 188 million unintended pregnancies, which in turn results in 112 million fewer abortions. Of the 867 million women in the developing world who are sexually active and want to avoid becoming pregnant, about 222 million of them have an unmet need for modern contraception. Objectives: To identify the determinant factors for utilization of intra uterine contraceptive device among women visiting primary health care facilities in Mekelle city. Method: The facility based unmatched case-control study design was conducted among 234 women (78 cases and 156 controls). Data was collected by questionnaire. Data entry and cleaning was done using EPI- Info version 5.3.1 and analysis done using SPSS version 20. The study used a logistic regression model to identify the association between independent variables with Intra Uterine Contraceptive Device. Result: Marital status ([AOR (95%CI) =8.59(2.60 - 28.43)], number of pregnancies (AOR (95%) CI=5.69(1.020-31.802), and number of alive children [AOR (95%CI) =3.5 (1.03-11.9) had a significant association with the use of Intra Uterine Contraceptive Device. Other determinants found to have significant association includes awareness about Intra Uterine Contraceptive Device, visual exposure to Intra Uterine Contraceptive Device, and participants told about the availability of health care provider able to insert Intra Uterine Contraceptive Device. Conclusion: The study identified marital status, gravidity, number of alive children, information on availability of IUCD provider and visual exposure to IUCD and awareness to Intra Uterine Contraceptive Device as major determinants for use of Intra Uterine Contraceptive Device. Thus, stake holders like Tigray Regional health bureau, health care facilities and others stakeholder should work to strength in service quality to increase the utilization of this effective and safe modern contraceptive method IUCD. Key word: Case control, Determinant factors, Intra Uterine Contraceptive Device, Logistic regression